Evaluation Instruments of Dance Learning Outcomes Based on Theory of Multiple Intelligences in Elementary School - Siswantari, Heni; Maretha, Anugrah (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2020)
This evaluation instrument is an instrument that emphasizes multiple intelligences that are used to assess the process and results of dance learning. This study aims to develop and find out the quality of evaluation instruments for dance learning outcomes based on multiple intelligences in elementary school students. This research is a type of Research and Development (RnD) development research using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development models. This research was tested on the fourth grade teachers of a private Islamic elementary school in Bantul City. Data collection techniques using expert validation sheets and teacher assessment sheets, then analyzed using quantitative data and qualitative data. The results of this study indicate that research and development has been carried out using the ADDIE model. The results of the assessment of learning experts get a value of 92.5 in the excellent category, material experts get a score of 94 in the excellent category, the evaluation expert gets a score of 77.5 in the good category, and the teacher's test scores 95 in the excellent category. Thus the average of all ratings scored 93.83 in the excellent category. Based on the test, the validity of the questions met the valid criteria. The reliability of multiple choice questions was 0.58 with sufficient criteria and description of 0.67 with sufficient criteria. So the instrument for evaluating dance learning outcomes based on multiple intelligences has good quality.